2020
DOI: 10.1007/s42452-020-03394-7
|View full text |Cite
|
Sign up to set email alerts
|

Andrographis paniculata-mediated synthesis of silver nanoparticles: antimicrobial properties and computational studies

Abstract: The present work reports a simple-economical procedure for the formation of silver nanoparticles by using controlled addition of concentration of cetyltrimethylammonium bromide (CTAB) as a capping agent, taking one-factor-at-a-time into consideration during the optimization process. Wet chemical method for silver(I) reduction has been used to synthesize nanoparticles using Andrographis paniculata. During the reaction, antioxidant property of biosystem reduces silver(I) to metallic silver(0) and CTAB encapsulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Recently, nanoscience and technology have developed rapidly all over the world, largely by adopting the quality, advancement, and efficiency of nanoparticles [1,2]. The transition of metal nano-materials grabbed the attention of researchers due to massive applications in the field of environmental sciences, biomedical sciences, and electrochemical sciences [2][3][4][5][6][7][8]. The physical and chemical methods of synthesis of nanoparticles have limited advantages due to high toxicity [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nanoscience and technology have developed rapidly all over the world, largely by adopting the quality, advancement, and efficiency of nanoparticles [1,2]. The transition of metal nano-materials grabbed the attention of researchers due to massive applications in the field of environmental sciences, biomedical sciences, and electrochemical sciences [2][3][4][5][6][7][8]. The physical and chemical methods of synthesis of nanoparticles have limited advantages due to high toxicity [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that andro-AgNPs exhibit excellent antibacterial activity, as demonstrated by their low MIC and MBC values in the nM range. This is consistent with previous studies that evaluated the antimicrobial activity of AgNPs synthesized using Andrographis paniculata extract. , Those studies showed that the AgNPs were effective against a variety of bacteria, including S. aureus, E.…”
Section: Resultsmentioning
confidence: 99%
“…Rajakumar et al synthesized zinc oxide nanoparticles by exploiting the reducing and capping potential of A. paniculata leaf extract (Rajakumar et al 2018 ). Anantharaman et al used leaf extract of A. paniculata for the synthesis of AgNPs and evaluated its anti-microbial properties (Anantharaman et al 2020 ). Biological synthesis of titanium dioxide nanoparticles was carried out with leaves extract of A. paniculata by Rajeshkumar et al ( 2021 ).…”
Section: Resultsmentioning
confidence: 99%